Cross-linked Ni(OH)2/CuCo2S4/Ni networks as binder-free electrodes for high performance supercapatteries. Issue 44 (6th November 2018) - Tang, Ning; You, Huihui; Li, Ming; Chen, George Zheng; Zhang, Lei
Abstract : The cross-linked networks can achieve much improved electrochemical performance and cycling stability, demonstrating the feasibility and effectiveness of structure engineering. Abstract : The heterogeneous Ni(OH)2 /CuCo2 S4 /Ni electrode is constructed by appropriately adjusting the time-dependent hydrothermal and electrodeposition process. A hybrid device exhibits 39.7 W h kg −1 of specific energy and 365.3 W kg −1 of specific power, with a good cycling stability of 88% capacity retention after 5000 cycles at 6 A g −1 .